Transformation and Re-Creation: Creating Spaces for Indigenous Theorising in Canadian Aboriginal Studies Programs - Deborah Mcgregor (The Australian Journal of Indigenous Education, 2005)
Abstract This paper explores the professional experience of an Anishnabe educator working in various organisations teaching Indigenous knowledge issues in both Aboriginal and primarily non-Aboriginal settings. The reflections span a number of years of teaching Aboriginal worldview and knowledge issues courses and include formal evaluations from both Aboriginal and non-Aboriginal students who have participated in the courses over that time. This paper draws upon two examples of educational institutions where Indigenous knowledge is being explored: the University of Toronto’s Aboriginal Studies Program and the Centre for Indigenous Environmental Resources’ (CIER) National First Nations Youth Environmental Education and Training Program. Both settings represent special places for thinking about decolonising Indigenous education. Integral to Aboriginal philosophy and decolonising education is the role elders play in informing and implementing meaningful education for Aboriginal learners. Both programs involve elders in central roles where they are recognised as authorities, facilitators and teachers. Discussion is offered on the subject of Aboriginal philosophies pertaining to education and some models for acting upon them, particularly as they relate to environmental education. Further analysis summarises the challenges faced by both programs and initiatives taken to advance Aboriginal educational goals. Finally, recommendations are made as to the types of changes which may be undertaken to realise creative spaces for resistance and creativity.